(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Skin health and complexion improvement have become more prioritized and the need for natural remedies are more in demand than the synthetic options. Research in the area of skin care is growing with regular updation of facts and data. In Ayurveda, skin complexion improvement is comparable to the modern concepts such as tyrosinase inhibition and anti-oxidant activity. In this review, selected Ayurvedic medicinal plants are screened from classical Ayurvedic texts as well as the modern scientific literature to investigate their probable potential for skin health and skin lightening effects. All the plants reviewed are found to act as complexion promoters directly or indirectly by their interference in melanogenesis pathway or through antioxidant potentials. This efficiently confirms the goodness of these plants as potential skin care and whitening agents.